2022
DOI: 10.1093/mtomcs/mfac036
|View full text |Cite
|
Sign up to set email alerts
|

Bioconjugated chelates based on (methylpyridinyl)tacn: synthesis, 64Cu labeling and in vitro evaluation for prostate cancer targeting

Abstract: Three new bifunctional copper chelators based on the 1,4,7-triazacyclononane (tacn) platform have been synthesized and conjugated to peptide. The first one is constituted of the tacn with two methylpyridinyl and one methylthiazolyl carboxylic acid pendant arms, while, in the second and third ones, the macrocycle is functionalized by three methylpyridinyl groups, with an additional hexynoic acid chain on a carbon of one or two pyridine rings. These three bifunctional chelators have been conjugated to the antago… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…For instance, phosphonic acid, phosphinic acid, and imidazole pendants have been incorporated into several gallium­(III) chelators, including on the tacn backbone, with varying degrees of success. Some authors also reported chelating platforms functionalized with picolinic acid pendants, which present a high affinity for trivalent hard metal ions such as Sc 3+ , Ga 3+ , and In 3+ and demonstrate very attractive coordination properties toward these metal cations. , We and others also contributed to the development of azamacrocycles with picolinate-based pendants for different cations, including different radionuclides. These bidentate functions present several advantageous coordination properties thanks to their rigidity and to the five-membered chelate rings that are formed with the aromatic nitrogen, the carboxylate oxygen, and the coordinated metal. Additionally, the hard acidic character of gallium­(III) well matches the combination of hard and borderline base characters of the oxygen and pyridinyl nitrogen atoms.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, phosphonic acid, phosphinic acid, and imidazole pendants have been incorporated into several gallium­(III) chelators, including on the tacn backbone, with varying degrees of success. Some authors also reported chelating platforms functionalized with picolinic acid pendants, which present a high affinity for trivalent hard metal ions such as Sc 3+ , Ga 3+ , and In 3+ and demonstrate very attractive coordination properties toward these metal cations. , We and others also contributed to the development of azamacrocycles with picolinate-based pendants for different cations, including different radionuclides. These bidentate functions present several advantageous coordination properties thanks to their rigidity and to the five-membered chelate rings that are formed with the aromatic nitrogen, the carboxylate oxygen, and the coordinated metal. Additionally, the hard acidic character of gallium­(III) well matches the combination of hard and borderline base characters of the oxygen and pyridinyl nitrogen atoms.…”
Section: Introductionmentioning
confidence: 99%